Comparative Transcriptome Analysis Reveals the Process of Ovarian Development and Nutrition Metabolism in Chinese Mitten Crab, Eriocheir Sinensis - Feng, Qiangmei; Liu, Meimei; Cheng, Yongxu; Wu, Xugan (Frontiers in Genetics, 2022)
Ovarian development is a key physiological process that holds great significance in the reproduction of the Chinese mitten crab (Eriocheir sinensis), which is an economically important crab species for aquaculture. However, there is limited knowledge for the regulatory mechanisms of ovarian development. To study the molecular mechanisms of its ovarian development, transcriptome analysis was performed in the ovary and hepatopancreas of E. sinensis during ovarian stages I (oogonium proliferation), II (endogenous vitellogenesis), and III (exogenous vitellogenesis). The results showed that 5,520 and 226 genes were differentially expressed in the ovary and hepatopancreas, respectively. For KEGG enrichment analysis, the differentially expressed genes in the ovary were significantly clustered in phototransduction-fly, phagosome, and ECM-receptor interaction. Significantly enriched pathways in the hepatopancreas included fatty acid biosynthesis, fatty acid metabolism, and riboflavin metabolism. Further analysis showed that 25 genes and several pathways were mainly involved in oogenesis, including the ubiquitin-proteasome pathway, cyclic AMP-protein kinase A signaling pathway, and mitogen-activated protein kinase signaling pathway. Twenty-five candidate genes involved in vitellogenesis and endocrine regulation were identified, such as vitellogenin, vitellogenin receptor, estrogen sulfotransferase, ecdysone receptor, prostaglandin reductase 1, hematopoietic prostaglandin D synthase and juvenile hormone acid O-methyltransferase. Fifty-six genes related to nutritional metabolism were identified, such as fatty acid synthase, long-chain-fatty-acid-CoA ligase 4, 1-acyl-sn-glycerol-3-phosphate acyltransferase 4, fatty acid-binding protein, and glycerol-3-phosphate acyltransferase 1. These results highlight the genes involved in ovarian development and nutrition deposition, which enhance our understanding of the regulatory pathways and physiological processes of crustacean ovarian development.